NGINX cookbook : make the most of your web server - Butler, Tim (Packt Publishing, 2017)
A practical book on real-world NGINX deployments to get you up and running quickly. About This Book Be the first to immerse yourself in the NGINX 1.9x web server and explore the plethora of advanced features. Master the skills of load balancing TCP-based applications and implementing HTTP/2. A recipe-based approach book that provides you with up-to-date information on NGINX, allowing you to implement specific use cases immediately. Who This Book Is For This book is aimed at smaller-to-medium developers, who are just getting started with NGINX. It assumes they already understand the basics of how a web server works and how basic networking works. What You Will Learn Practical, real-world examples and recipes on how to use NGINX Common CMS deployments such as WordPress, Joomla and more NGINX configurations for frameworks such as Ruby on Rails, Django and more Detailed SSL recipes, including HTTP/2 Real world rewrite examples Basic web and TCP load balancing configuration Bandwidth management and connection limiting Detailed NGINX deployment scenarios with Docker Performance tuning and monitoring of your NGINX deployments OpenResty deployment guides Advanced deployments with NGINX Plus features In Detail NGINX Cookbook covers the basics of configuring NGINX as a web server for use with common web frameworks such as WordPress and Ruby on Rails, through to utilization as a reverse proxy. Designed as a go-to reference guide, this book will give you practical answers based on real-world deployments to get you up and running quickly. Recipes have also been provided for multiple SSL configurations, different logging scenarios, practical rewrites, and multiple load balancing scenarios. Advanced topics include covering bandwidth management, Docker container usage, performance tuning, OpenResty, and the NGINX Plus commercial features. By the time you've read this book, you will be able to adapt and use a wide variety of NGINX implementations to solve any problems you have.